From the Germanic to the Soviet Accounting System (History of Czechoslovak Accounting after the World War Two) - Vladimír Zelenka; Marie Zelenková (European Financial and Accounting Journal, 2013)
The development of accounting in Czechoslovakia after the World War II was influenced by political and economic changes of that time. Firstly, it is a subject to tradition, and then also the political order. It results in the transition from the Germanic type of accounting to the Soviet model of accounting, i.e. from the Singular System of Business Accounting to Book-Keeping Evidence under the National-Economic Evidence. Although the Soviet accounting system is by some formal characteristics based on the Anglo-Saxon model of accounting, it was unable to operate efficiently in terms of collectivist economies of the communist regime, i.e. neither in Czechoslovakia.
Keywords: M41; 650; Accounting History; Czechoslovak Accounting; Socialist Accounting